Penggunaan Media Pembelajaran Audiovisual untuk Meningkatkan Motivasi Belajar Siswa Kelas III pada Pembelajaran IPAS - Rochmania, Dia Ayu; Asmaul Lutfauziah; Muhammad Thamrin Hidayat; Afib Rulyansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of learning motivation among grade III students in IPAS (Integrated Natural Science and Social Science) learning. This is due to the teaching method still relying on lectures and the absence of learning media in IPAS classes. This study aims to determine the improvement of student learning motivation in IPAS learning after the use of audiovisual animation learning media. The research method used is quantitative with a one-group pre-test post-test design. The population in this study is all grade III students. The sample is determined using purposive sampling. The instrument used is a student learning motivation questionnaire based on the Likert scale. Data analysis uses N-Gain test with the help of Excel application. The research results are as follows: (1) The students' learning motivation before the use of audiovisual learning media in the IPAS lessons in grade III on the topic 'Recognizing Animals in the Surroundings' was categorized as poor. After the implementation of audiovisual learning media, the average post-test score of the students' learning motivation improved to a good category. (2) There was an increase in students' learning motivation after the application of audiovisual media in IPAS lessons in grade III. (3) Students' responses to the use of audiovisual learning media showed a very positive category.